Metabolism of lymphocyte populations in healthy children and patients with immune-dependent diseases - S. V. Petrichuk; O. V. Kurbatova; D. G. Kuptsova; T. V. Radygina; E. V. Freidlin (Аллергология и Иммунология в Педиатрии, 2023)
.